Anteseden Nilai Perusahaan Pada Perusahaan yang Konsisten Terdaftar di Jakarta Islamic Index (JII) - Rico Nur Ilham; Nelly Ervina; Julyanthry Julyanthry; Debi Eka Putri (Universitas Batanghari, 2022)
This study aims to examine the factors that can affect firm value. These factors include liquidity, capital structure, profitability and company size. This research was conducted on companies that were consistently listed on the Jakarta Islamic Index (JII) for the 2016-2020 period using secondary data and an associative research approach. The population in this study were all companies listed on the JII index company. The sample obtained is 11 companies using purposive sampling using certain criteria and has 55 observations. The results showed that liquidity and profitability had a significant effect on firm value partially, while capital structure and firm size had no significant effect on firm value. However, simultaneously all variables have an effect on firm value.